The slippery slope - Critical perspectives on in vitro research methodologies - Kelly, J. Robert; Benetti, Paula [UNESP]; Rungruanganunt, Patchanee; Della Bona, Alvaro (Elsevier B.V., 2012)
Objectives. This paper attempts to provide critical perspectives on common in vitro research methodologies, including shear bond testing, wear testing, and load-to-failure tests. Origins of interest in high-quality laboratory data is reviewed, in vitro data is categorized into property and simulation protocols, and two approaches are suggested for establishing clinical validity. It is hoped that these insights will encourage further progress toward development of in vitro tests that are validated against clinical performance and/or by producing clinically validated failure or damage mechanisms.Materials and methods. Published shear and tensile bond data (macro and micro) is examined in light of published finite element analyses (FEA). This data is subjected to a Weibull scaling analysis to ascertain whether scaling is consistent with failure from the bonded interface or not. Wear tests results are presented in light of the damage mechanism(s) operating. Quantitative wear data is re-examined as being dependent upon contact pressure. Load-to-failure test results are re-analyzed by calculating contact stresses at failure for 119 tests from 54 publications over more than 25 years.Results. FEA analyses and reported failure modes (adhesive, mixed, cohesive) are consistent with failure not involving interfacial "shear stresses" as calculated in published work. Weibull scaling clearly suggests failure involving external surfaces of specimens, not interfacial origins. Contact stresses (pressures) are clearly an important variable in wear testing and are not well-controlled in published work. Load-to-failure tests create damage not seen clinically due to excessively high contact stresses. Most contact stresses in the 119 tests examined were calculated to be between 1000 MPa and 5000 MPa, whereas clinical contact stresses at wear facets have been measured not to exceed 40 MPa.Conclusions. Our community can do a much better job of designing in vitro tests that more closely simulate clinical conditions, especially when contact is involved. Journals are encouraged to thoughtfully consider a ban on publishing papers using bond tests and load-to-failure methods that are seriously flawed and have no clinical relevance. (C) 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: In vitro; Bond; Shear; Failure testing; Clinical relevance